On the multiplicative order of elements in Wiedemann’s towers of finite fields - Popovych, R. (Carpathian Mathematical Publications, 2015)
We consider recursive binary finite field extensions E_i+1 =E_i (x_i+1 ), i-1, defined by D. Wiedemann. The main object of the paper is to give some proper divisors of the Fermat numbers N_i that are not equal to the multiplicative order O(x_i ).